Odnos Slavka Osterca do ljudske pesmi in nacionalizma v glasbi - Bedina, Katarina (Traditiones (Ljubljana), 1999)
In Slovenia the disintegration of the Austro-Hungarian monarchy led to the belief that in the newly-liberated state of the Serbs, Croats, and Slovenes composers would be faced with equally new tasks. Slavko Osterc was in favor ofa thorough research of the original Slovene music based on Slovene folk music. He perceived the perspective of Slovene music only within a conscious nationalistic confinement. On the other hand Marij Kogoj and Stanko Vurnik, who was an art historian with musical education, defended cosmopolitan music control and perfect ideological freedom of the creative process. Since the debate had been concluded before he has completed his stuudies in Prague Slavko Osterc did not participate in it. He placed folk songs on the highest rung of aesthetics, feeling that they were an authorial creation and that noone should have any right to them except if one wanted to further stress their musical value through a good arrangement. Osterc rejected the use of folk elements in art music; he was of the opinion that a composer had to draw ideas from his own creative imagination and build his composition technique on the experience of contemporary composers. His most ardent opposers were Croatian composers Anton Dobrunič and Boris Papandopulo. They criticized Osterc, maintaining that his music had no Slovene roots and that Slovene musiccould not identify itself with cosmopolitan views. Osterc defended himself and concluded the discussion on music nationalism after the example of Anton Lajovic, trying to prove that the music identity of Slovenes existed independently of any exterior citations of folk melodies.
Keywords: Osterc, Slavko, 1895-1941; slovenska glasba; folk music; ljudska glasba; glasbeni nacionalizem